Development of a validated computational fluid dynamics model for film cooling efficiency calculation - Shevchuk, Oleg; Tarasov, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates the film cooling process on a flat plate. The task addressed relates to the identification of the most universal CFD model for different film cooling hole shapes. The task has been solved by selecting an optimal computational mesh and determining the most suitable turbulence models for predicting film cooling effectiveness over a wide range of parameters. To investigate mesh‑independence effects, four levels of polyhedral computational grids were generated. It was shown that the mesh with 5.8 million elements, selected based on the mesh‑convergence analysis, performs nearly as well as a block‑structured mesh with identical settings. A validated CFD model based on a polyhedral mesh was built. A distinctive feature of the results is that the CFD model covers 4 hole geometries spaced 5D apart and inclined at 30° to the mainstream flow (classical cylindrical, fan‑shaped, oval, and a diffused slot). The results include a comparison of seven RANS turbulence models with experimental data. It was found that for the considered flow and geometric conditions, the most robust and generally applicable model is the k‑ε Realizable turbulence model. Its advantages may be explained by its improved stability and better sensitivity to regions of complex flow kinematics, which enables more accurate prediction of expanding (fan‑shaped and diffuser‑type) holes. Additionally, the model feasibility was verified for the 7-7-7 hole configuration. For this type of hole, a preliminary analysis of the influence of thermal barrier coating configurations on film cooling effectiveness is presented. The proposed computational model could be used for optimizing hole geometry and blowing conditions in gas turbine blade cooling applications